MENELUSURI SEJARAH ASAL MULA BALIKPAPAN MELALUI PERAYAAN ERAU BALIK DELAPAN Sebuah Kajian Budaya dan Folklor - Ulum Janah (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2012)
The study on the origin of Balikpapan City through Erau Balik Delapan is factually encouraged by the cultural phenomenon along Melawai Beach. The cultural phenomenon happens there has not yet found before which has been a specific interest of the new-comers. It has been beleived that Balikapan City does not have its own culture, rather than imigrants’ ones. While Erau is originated from East Kalimantan which is celebrated in areas away from East Kalimnatan, but not in Balikpapan. This ceremony is coducted with the presence of the King, the Queen, and the Kingdom’s Advisor of Kutai, which is then beleived that there is a close relationship between Kutai Kingdom and Erau in Balikpapan. This research is attempted to bring about thorough explanation about the history of Balikpapan City under qualitataive research method. The data are drawn through participatory observation, in-depth interview and documentation. The data are validated by the time-triangulation technique. The result of the reserach shows the origin of Balikpapan through Erau Balik Delapan pertaining to the history, culture and legend which are still depply rooted in the community of Kutai.